Measurement of CP asymmetries in D± → η′π± and D±s → η′π± decays - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Elsevier, 2017)
A search for $CP$ violation in $D^{±}→ η^{′} π^{±}$ and $D^{±}_{s}→ η^{′} π^{±}$ decays is performed using proton-proton collision data, corresponding to an integrated luminosity of $3$ fb$^{-1}$, recorded by the LHCb experiment at centre-of-mass energies of $7$ and $8$ TeV. The measured $CP$-violating charge asymmetries are $A_{CP}(D^{±} → η^{′} π^{±})=(-0.61± 0.72 ± 0.53 ± 0.12)%$ and $A_{CP}(D^{±}_{s}→ η^{′} π^{±})=(-0.82± 0.36 ± 0.22 ± 0.27)%$, where the first uncertainties are statistical, the second systematic, and the third are the uncertainties on the $A_{CP}(D^{±} → K^0_S π^{±})$ and $A_{CP}(D^{±}_{s}→ φ π^{±})$ measurements used for calibration. The results represent the most precise measurements of these asymmetries to date.